SECTORAL PORTFOLIO STRATEGIES TO SUSTAIN GROWTH DURING HIGH INFLATIONARY PERIOD IN INDONESIA STOCK EXCHANGE - Trisnawati Maitreya; Victor Chandra (Journal of Business Strategy and Execution, 2015)
Previous studies proposed that there is negative correlation between inflation and stock return. The negative correlation is assumed driven by expectations in the increasing of nominal risk free rate return thus accelerating demand of money. This assumption is in accordance with stock valuation perspective in which lower stock valuation will move in tandem with the increase of risk free rate. Given the rising inflation in Indonesia nowadays, this research is intended to improve investor’s decision in hedging against inflation.          This research proposes asset pricing models with inflation factor by conducting portfolio using selective industry sectors approach. The intention is intended to discover hedging ability of some industry sectors against inflation. Accordingly can helps investors to improve investment decisions in stabilizing investment return throughout inflationary period. Research model is evaluated using single index model, reward-risk ratio and maximum drawdown strategy in Indonesia stock market.The result of this study based on asset pricing models with inflation factor shown that consumer, property, and basic industry sectors have the potential to provide a much better inflation hedge in highinflationary period. These sectors are positively correlated with inflation in 0.05 level of significant.